2013
DOI: 10.1111/cdev.12038
|View full text |Cite
|
Sign up to set email alerts
|

Daily Intragroup Contact in Diverse Settings: Implications for Asian Adolescents' Ethnic Identity

Abstract: This study examined the daily-level association between contact with same-ethnic others and ethnic private regard among 132 Asian adolescents (mean age 14) attending 4 high schools ranging in ethnic composition diversity. The data suggest a positive daily-level association between contact with same-ethnic others and ethnic private regard for adolescents who were highly identified with their ethnic group and who attended predominantly White or ethnically heterogeneous schools. In addition, using time lag analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
78
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(80 citation statements)
references
References 55 publications
0
78
0
Order By: Relevance
“…Studies with Latino and African American adolescents showed that friendships with same-ethnic peers were associated with stronger sense of ethnic identity (e.g., Graham et al, 2014; Syed & Juan, 2012). Perhaps the shared experiences of being an ethnic minority in American society, such as similar encounters with discrimination, that are discussed among same-ethnic friends can heighten adolescents’ sense of who they are and their identification with their ethnic group (Phinney, Romero, Nava, & Huang, 2001; Yip, Douglass, & Shelton, 2013). …”
Section: Functions Of Different Friendship Typesmentioning
confidence: 99%
“…Studies with Latino and African American adolescents showed that friendships with same-ethnic peers were associated with stronger sense of ethnic identity (e.g., Graham et al, 2014; Syed & Juan, 2012). Perhaps the shared experiences of being an ethnic minority in American society, such as similar encounters with discrimination, that are discussed among same-ethnic friends can heighten adolescents’ sense of who they are and their identification with their ethnic group (Phinney, Romero, Nava, & Huang, 2001; Yip, Douglass, & Shelton, 2013). …”
Section: Functions Of Different Friendship Typesmentioning
confidence: 99%
“… 2 Findings from this data set have been published (Yip, Douglass, & Shelton, 2013), but there is no overlap with this article. …”
mentioning
confidence: 97%
“…Individual differences such as the importance of one’s race/ethnicity (e.g., racial/ethnic identity centrality) likely influence how meaningful interactions with same-racial/ethnic others are by making the interactions more or less relevant to one’s self-views and well-being (Yip et al 2013). Further, for youths, schools are important structural contexts offering varying opportunities for contact with same- and different- racial/ethnic others, depending on the diversity of the school.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Asian American college students who have high levels of centrality report being more aware of their race/ethnicity on days they are surrounded by more Asians (Yip 2005). Similarly, Asian American adolescents who have high levels of centrality report feeling more positive about their racial/ethnic group than their peers with low centrality on days that they were surrounded by more Asians, particularly when they are underrepresented in their school settings (Yip et al 2013). However, research has not yet considered how centrality may influence the relationship between intragroup contact and non-identity outcomes, such as anxiety symptoms.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation